Echocardiographic evaluation of the size of the main pulmonary artery and right pulmonary artery in dogs with pulmonary hypertension - Giovanni Grosso; Rosalba Tognetti; Oriol Domenech; Andrea Della Pina; Federica Marchesotti; Valentina Patata; Tommaso Vezzosi (Journal of Veterinary Internal Medicine)
Abstract Background Evaluating the size of the pulmonary artery (PA) is key for the echocardiographic assessment of pulmonary hypertension (PH) in dogs. Hypothesis/Objectives To compare the diagnostic accuracy of the main PA (MPA) and right PA (RPA) sizes for the echocardiographic detection of PH in dogs, and to evaluate differences between precapillary and postcapillary PH dogs. Animals Four hundred four dogs; 136 controls and 268 with PH. Methods Prospective, multicenter, observational study. The MPA, maximum and minimum RPA diameter were normalized to body weight (MPA_N, RPAmax_N, and RPAmin_N). The MPA was also indexed to the ascending aorta (MPA/AO), while the RPA size was indexed to the aortic annulus (RPAmax/Aod and RPAmin/Aod). The right pulmonary artery distensibility index (RPADi) was also calculated. The diagnostic accuracy of PA parameters for PH was assessed through the receiver operating characteristic curve analysis and area under the curve (AUC). Measurement variability was assessed trough the coefficient of variation (CV). Results The RPADi, RPAmin_N, and RPAmin/Aod showed similar diagnostic accuracy for the detection of PH (AUC = 0.975, AUC = 0.971, and AUC = 0.953, respectively), higher than MPA/AO (AUC = 0.926), MPA_N (AUC = 0.880), RPAmax_N (AUC = 0.814), and RPAmax/Aod (AUC = 0.803; P < .05). Aside from RPAmax variables, no differences were found between precapillary and postcapillary PH. RPA size parameters showed lower CVs in comparison to MPA/AO and RPADi. Conclusions and Clinical Importance Although MPA/AO showed an excellent sensitivity and specificity for the detection of PH, the RPAmin exhibited a higher diagnostic accuracy and less measurement variability, thus could represent a new useful parameter for the detection of PH in dogs.